2022
DOI: 10.1038/s41467-022-28985-3
|View full text |Cite
|
Sign up to set email alerts
|

The methyl phosphate capping enzyme Bmc1/Bin3 is a stable component of the fission yeast telomerase holoenzyme

Abstract: The telomerase holoenzyme is critical for maintaining eukaryotic genome integrity. In addition to a reverse transcriptase and an RNA template, telomerase contains additional proteins that protect the telomerase RNA and promote holoenzyme assembly. Here we report that the methyl phosphate capping enzyme (MePCE) Bmc1/Bin3 is a stable component of the S. pombe telomerase holoenzyme. Bmc1 associates with the telomerase holoenzyme and U6 snRNA through an interaction with the recently described LARP7 family member P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Our previous work characterizing Bmc1 as a component of the telomerase holoenzyme also revealed interactions between Bmc1 and various other noncoding RNAs, including the U6 snRNA (Figure S1A) (20). We therefore tested whether Bmc1 has a role in the biogenesis, stability, or function of these transcripts, and if this function is linked to the Bmc1-interacting telomerase components Pof8 and Thc1.…”
Section: Bmc1 Forms a U6-containing Complex With The Telomerase Prote...mentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous work characterizing Bmc1 as a component of the telomerase holoenzyme also revealed interactions between Bmc1 and various other noncoding RNAs, including the U6 snRNA (Figure S1A) (20). We therefore tested whether Bmc1 has a role in the biogenesis, stability, or function of these transcripts, and if this function is linked to the Bmc1-interacting telomerase components Pof8 and Thc1.…”
Section: Bmc1 Forms a U6-containing Complex With The Telomerase Prote...mentioning
confidence: 95%
“…Having already demonstrated that Pof8 is required to recruit Bmc1 to the telomerase RNA TER1 (20), we determined the protein binding requirements for U6. In contrast to what has been reported for TER1, for which reduced binding to Pof8 persists in the absence of Bmc1 (20,34), we found that all three proteins are necessary for an interaction with U6 (Figure 1A, S1B). Our results indicating an interaction between Pof8 and U6 are also consistent with previous work identifying mammalian LARP7 as a U6-interacting protein (26,27), suggesting that LARP7 family members have conserved functions related to U6, in addition to the established evolutionary conservation of LARP7 in telomerase (29)(30)(31).…”
Section: Bmc1 Forms a U6-containing Complex With The Telomerase Prote...mentioning
confidence: 99%
See 3 more Smart Citations